2009
DOI: 10.1001/archgenpsychiatry.2008.513
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Informed Study of the Association Between Childhood Separation Anxiety, Sensitivity to CO2, Panic Disorder, and the Effect of Childhood Parental Loss

Abstract: Shared genetic determinants appear to be the major underlying cause of the developmental continuity of childhood separation anxiety disorder into adult panic disorder and the association of both disorders with heightened sensitivity to CO(2). Inasmuch as childhood parental loss is a truly environmental risk factor, it can account for a significant additional proportion of the covariation of these 3 developmentally related phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 52 publications
5
88
1
4
Order By: Relevance
“…Best-fit solutions from all three computational approaches, however, correspond in suggesting a role for shared environmental factors in affecting the risk for Anxiety and Affective Problems in children aged 8-11 years, consistently with recent epidemiological-, quantitative genetic-, and molecular genetic studies [4,14,33]. Clinicians may therefore pay special attention in assessing the presence of environmental risk/precipitating factors in children who are referred for these disorders.…”
Section: Resultssupporting
confidence: 57%
“…Best-fit solutions from all three computational approaches, however, correspond in suggesting a role for shared environmental factors in affecting the risk for Anxiety and Affective Problems in children aged 8-11 years, consistently with recent epidemiological-, quantitative genetic-, and molecular genetic studies [4,14,33]. Clinicians may therefore pay special attention in assessing the presence of environmental risk/precipitating factors in children who are referred for these disorders.…”
Section: Resultssupporting
confidence: 57%
“…Battaglia et al reported three experiments [86][87][88] in which another variable was added to the twins' equation: the occurrence of traumatic events such as those leading to childhood separation anxiety, death of parents, and a history of generally stressful situations in childhood. The first of these, 86 with 700 twins, suggested the existence of a continuum of childhood separation anxiety and PD, and the association of both disorders with hypersensitivity to CO 2 .…”
Section: Twin Studiesmentioning
confidence: 99%
“…The first of these, 86 with 700 twins, suggested the existence of a continuum of childhood separation anxiety and PD, and the association of both disorders with hypersensitivity to CO 2 .…”
Section: Twin Studiesmentioning
confidence: 99%
“…Early-life experiences may have long-term consequences (42)(43)(44)(45)(46) and have been associated to functional and morphological abnormalities in brain regions connected with emotionality such as the amygdala, the hippocampus, and the prefrontal cortex (47,48).…”
Section: Models Of Environmental Manipulationmentioning
confidence: 99%
“…Human studies show that SAD predicts heightened risk to develop PD in adulthood (75,76) and both these conditions are associated with heightened sensitivity to CO 2 (44,77,78). In turn, CO 2 hypersensitivity shares common genetic determinants with both SAD and PD, with childhood parental loss adding a significant contribution to explain covariation (44).…”
Section: Endophenotype Levelmentioning
confidence: 99%